How Does the Arctic Council Support Conservation of Arctic Biodiversity? - Tom Barry; Brynhildur Daviðsdóttir; Níels Einarsson; Oran R. Young (Sustainability, 2020)
The Arctic Council is an intergovernmental forum promoting cooperation, coordination and interaction among Arctic states, indigenous communities, and peoples on issues of common importance. The rising geo-political importance of the Arctic and the onset of climate change has resulted in the Council becoming a focus of increasing interest from both inside and beyond the Arctic. This has resulted in new demands placed on the Council, attracting an increasing number of participants, and instigating a period of transformation as Arctic states work to find a way to balance conflicting demands to improve the Council’s effectiveness and take care of national interests. This paper considers whether, during this time of change, the Council is having an impact on the issues it was formed to address, i.e., environmental protection and sustainable development. To provide answers, it looks at how the Council reports on and evaluates progress towards the implementation of recommendations it makes regarding biodiversity, how it identifies where activities have had impacts and uncovers the mechanisms through which they were successful, to provide an insight into how the Arctic Council can be an agent of change.